Redesign Improved Employees Performance of Corporate Textile - Anton Respati Pamungkas; Ida Ayu Brahmasari; Siti Mujanah (Sebelas Maret Business Review, 2018)
This research aims to redesign improved employees’ performance of corporate textile in terms of compensation, competence, quality of work-life and organizational citizenship behavior. The method used in this research is a survey conducted on the employees of a textile factory. Employees who serve the population of this study is diversified from the level of staff to the Director. The sample is 245 respondents. Data analysis and hypothesis test in this study using the Structural Equation Model - Partial Least Square (PLS-SEM). The results showed that each variable compensation, competence, quality of work-life and organization citizenship behavior has a positive and significant impact on employee performance. Variable organization citizenship behavior can be variable which can improve the effect of compensation, competence and quality of work-life toward employees’ performance.